Farmers' Coping Strategy in Maintaining Household Economic Stability in the Dry Season: A Sharia Economic Perspective - Zahroh, Fatimatus; Muktirrahman, Muktirrahman; Maksum, Maksum (Danadyaksa: Post Modern Economy Journal, 2025)
This study analyzes the coping strategies employed by farmers in Rombiya Barat Village, Ganding, to maintain household economic stability during the dry season from an Islamic economic perspective. Employing a qualitative approach, this research utilizes in-depth interviews with selected farmers through purposive sampling. The data were analyzed using a thematic approach to identify key survival strategies. The findings reveal three primary coping strategies: active strategies, passive strategies, and networking strategies. From an Islamic economic perspective, business diversification that adheres to the principles of halal and thayyib plays a crucial role in sustaining farmers’ economic resilience. Furthermore, the study highlights that food security among farmers is significantly influenced by socioeconomic conditions, natural resource management, and the practical implementation of Islamic economic principles. This research contributes to the understanding of Islamic economic-based rural resilience and offers policy insights for enhancing sustainable agricultural development.